Zur Neubestimmung von Geschichte und Theoriegeschichte in den Wirtschaftswissenschaften: Ko-evolution von Wirtschaftsbeobachtung und Wirtschaftswirklichkeit - Kurt Dopfer (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
Economic History and the History of Economic Thought haven been relegated increasingly from the teaching and research curricula of economics in recent years. The paper starts off arguing that this trend is due to the mechanistic ontology of mainstream economics, and it continues setting out an alternative evolutionary ontology expounding how the historical element must and can be integrated into the body of economic theory. Centre stage is a lingua franca composed of analytical terms that are designed to bridge the domains of theoretical and of historical economic analysis. Economists are viewed in their status as observers whose cognitive dispositions as well as social behaviour co-evolve with the environment they inhabit. Further advances in economic theory are seen as being critically dependent on employing an evolutionary approach and on establishing a communication link to economic history and the history of economic thought - which likewise may get essential inspirations from applying that approach.
Keywords: B10; B20; B25; N00; N01; 330; Neuroeeconomics; Behavioural Economics; Entscheidungsverhalten; Validierung ökonomischer Modelle; Wirtschaftswissenschaft; Dogmengeschichte